Desain Logo Responsif sebagai Identitas Visual DKV Universitas ‘Aisyiyah Bandung - Faizal, Mochammad (Universitas Komputer Indonesia, 2020)
The increasing use of the internet in Indonesia, especially during the Covid-19 pandemic, has become an issue that needs to be considered by institutions when designing the Desain Komunikasi Visual study program logo of the Universitas ‘Aisyiyah Bandung. This study aims to design a study program logo that is responsive when applied in various media, which emphasizes geometry shapes as an Islamic visual identity. The design process is done by qualitative methods using a linear design strategy. Data collection was carried out through a literature study, visual observation of three similar logos, and then analyzed using a comparison matrix. The result is a logo that is composed of geometric shapes, has a golden ratio, and has several alternative configurations that reflect its nature as a responsive logo on various digital media. This research can be an example to design other similar logos, especially in the scope of Universitas ‘Aisyiyah which is wrapped with Islamic nuances.